El intercambio de invectivas en yambos latinos entre Bonaventura Vulcanio y Franz Nans - Pino González, Eduardo del, 1966- (Humanistica lovaniensia: journal of neo-latin studies, 2021)
This paper consists of the first critical edition and translation of some Latin poems written in iambic meter by the Flemish Hellenists Bonaventura Vulcanius and Franciscus Nansius to attack each other. It also contains a commentary on their historical context, genre, meter, vocabulary and style.